Intermediate Institutions for Interactive Learning Processes in a Governance Perspective: the Case of Aeronautic Industry in Campania Region - Giuseppe Pace; Riccardo Cappellin; Immacolata Caruso (European Regional Science Association (ERSA), 2006)
The present paper presents the results of the empirical analysis on fifteen enterprises and twenty no-industrial organizations involved at different level in the Aeronautical Cluster in the Campania Region. Information and data on the selected sample are colleted both by a study of the industrial sector, and also by suitable questionnaires and interviews, that the authors have submitted to the entrepreneurs and to the top managers of either the enterprises or the no-industrial organizations. The authors have focalized their study by applying the SWOT analysis on the following issues: the cluster's structure by analysing the relational skill developed by single actors of the cluster and by their impact on the innovation capacity of the enterprises; the effectiveness of cluster's governance strategies and how different actors actually participate to the local development processes of the aeronautical industrial sector. On these bases the authors wanted to deduce possible policy options for different kind of actors to optimize the cluster's governance. Particularly they will describe in the present paper some indications to: 1) the SME's that present strong relations with customers but low integration with large part of the others actors, i.e. with no-customers enterprises; 2) the large enterprises related to the industrial policies and to the suppliers' governance; 3) the policy makers at local level and the intermediate institutions for a better support of the local enterprises. In fact, the research results are based on the conscientious awareness that the analyzed sector is at a critical point, for which it is necessary that all the actors involved put together their efforts in order to steer and to direct the development process, both by identifying participative mechanisms at local level and also by strengthening those exogenous elements which are able to promote local development. Obviously only part of the criticisms can be solved at local and national level and some of them can be solved only partially. This observation opens the question of policy at the international level which can be determinate only with a more exhaustive integration into transnational networks. The research described in the present paper has been undertaken within the framework of the project: "IKINET – International Knowledge and Innovation Network" (EU FP6, N° CIT2-CT-2004-506242).
Keywords: 330